Konsep Masyi’atu Allah Wa Masyi’atu Al-‘Ibad dan Implikasinya dalam Pendidikan Islam - Sidik, Fajar; Setia Budi, Firmansah; Ahmad, Nurwadjah; Suhartini, Andewi (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2024)
The concepts of "masyiatu Allah" (the will of Allah) and "masyiatu al-‘ibad" (the will of humans) are significant topics that have long been discussed and debated among theological schools such as Jabariyah, Qadariyah, and Ahlus Sunnah. Each school has its own differing opinions. This issue needs to be re-examined in relation to the implications of these differing opinions on the concept of education in Islam. This study is particularly important for Muslims who adhere to the Ahlus Sunnah creed, so that in understanding the educational process, they do not deviate from the Ahlus Sunnah understanding, or even adopt the understanding of Jabariyah and Qadariyah. This research aims to delve deeper into the concepts of "masyiatu Allah" and "masyiatu al-‘ibad" in the Islamic educational process from a theological perspective. This will be clarified through a comparison between the theological perspectives of the Jabariyah, Qadariyah, and Ahlus Sunnah schools. The method used in this research is qualitative, with a library research type (bahtsun maktabiy) using a descriptive analysis approach (dirasah washfiyah). The results of this study show that the Jabariyah school denies the will of humans (masyiatu al-‘ibad) in the educational process. Conversely, the Qadariyah school denies the will of Allah (masyiatu Allah) in the educational process. Meanwhile, Ahlus Sunnah does not deny either of them; Ahlus Sunnah believes that both have their respective roles in the educational process. Thus, education in Islam must be able to direct students so that their will aligns with what is willed by Allah -ta’ala-.